2012
DOI: 10.3341/kjo.2012.26.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Optic Neuritis in Koreans Greater than 50 Years of Age

Abstract: PurposeTo report clinical characteristics of optic neuritis (ON) in Koreans >50 years of age.MethodsA retrospective chart review was performed on patients with ON between January 2000 and December 2009. We obtained the best-corrected visual acuity (BCVA), Goldmann perimetry, relative afferent pupillary defect (RAPD), and color function tests as well as brain magnetic resonance imaging (MRI) findings in patients who were in the acute stage of the disorder.ResultsNine eyes in eight patients were included. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…A recent study, which is conducted in Korea, reported that patients > 50 years recovered well from ON attacks; all affected eyes had final BCVA > 20/40 within two months [ 15 ]. However, the small sample size, eight patients in total, may result in increase of the bias.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, which is conducted in Korea, reported that patients > 50 years recovered well from ON attacks; all affected eyes had final BCVA > 20/40 within two months [ 15 ]. However, the small sample size, eight patients in total, may result in increase of the bias.…”
Section: Discussionmentioning
confidence: 99%
“…NAION is a sight threatening disease that typically presents a painless and prompt loss of vision in the middleaged or elderly, which is associated to campimetric defects, being the most common type an inferior altitudinal defect, although other types may also be present, such as arcuate scotoma, central scotoma, blind-spot enlargement, and ring scotoma (Choi et al 2012;Hayreh and Zimmerman 2005). Depending on the severity of the NAION, some patients may experience a worsening, stabilisation, or improvement of their visual function, though, in general terms, NAION is associated to a poor prognosis due to the irreversible changes of the optic disc derived from temporally insufficient blood supply (Jung et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…There is a paucity of information describing the clinical profile of ON in middle-aged and elderly populations. To our knowledge, only three articles from China [ 2 , 7 ] and Korea [ 6 ] have described ON profiles in this age group in the Asian region. The ONTT and a few other studies reported female predominance among ON patients [ 2 , 4 , 9 ]; although the background of this observation is unclear, it was believed to be due to the twofold risk of developing a demyelinating disease (MS) in young women [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies describing ON features in populations older than 45 years of age. This can be due to the rarity of ON, and this is oftentimes misdiagnosed as non-arteritic anterior ischaemic optic neuropathy (NAION) due to the overlapping clinical profiles of these two diseases [ 6 ]. There are also inconsistent findings describing ON in middle-aged and elderly populations in China, Korea, and the US [ 2 , 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation